Uso antenatal de corticosteóide e evolução clínica de recém-nascidos pré-termo - Martinez, Francisco E.; Linhares, Nelson J.; Ferlin, Maria L. S.; Marba, Sérgio; Netto, Abimael A.; Procianoy, Renato S.; Uchoa, Natacha T.; Lopes, José Maria A.; Bomfim, Olga; Guinsburg, Ruth; Almeida, Maria Fernanda B.; Miyoshi, Milton; et al. (Fundacao Sociedade Brasileira de Pediatria, 2004)
Objectives: To describe the use of antenatal corticosteroid and clinical evolution of preterm babies. Methods: An observational prospective cohort study was carried out. All 463 pregnant women and their 514 newborn babies with gestational age ranging from 23 to 34 weeks, born at the Brazilian Neonatal Research Network units, were evaluated from August 1 to December 31, 2001. The data were obtained through maternal interview, analysis of medical records, and follow-up of the newborn infants. Data analysis was performed with the use of chi-square, t Student, Mann-Whitney, and ANOVA tests and multiple logistic regression, with level of significance set at 5%. Results: Treatment was directly associated with the number of prenatal visits, with maternal hypertension and with the antenatal use of tocolytic agents. Babies from treated pregnant women presented better Apgar scores at the 1st and 5th minute, reduced need for intervention in the delivery room and lower SNAPPE II. They were born with higher birth weight, longer gestational age and needed less surfactant use, ventilation, and oxygenation time. After multiple logistic regression, the use of antenatal corticosteroid independently improved birth conditions, decreased ventilation time, being related to increased occurrence of neonatal sepsis. Conclusions: The use of corticosteroid was associated with better prenatal care and birth conditions, better preterm evolution but higher risk of infection. Copyright © 2004 by Sociedade Brasileira de Pediatria.
Keywords: Antenatal glucocorticoids; Infection; Low birth weight; Mechanical ventilation; Prematurity; antibiotic agent; betamethasone; corticosteroid; dexamethasone; indometacin; surfactant; uterus spasmolytic agent; adult; analysis of variance; Apgar score; artificial ventilation; birth; chi square test; clinical trial; cohort analysis; controlled clinical trial; controlled study; delivery room; disease course; evaluation; female; follow up; gestational age; high birth weight; human; hyaline membrane disease; infant; interview; major clinical study; maternal hypertension; medical record; multivariate logistic regression analysis; necrotizing enterocolitis; newborn; newborn sepsis; oxygenation; pregnancy; prematurity; prenatal period; rank sum test; scoring system; Student t test; adolescent; blood; health care quality; infection; male; multicenter study; prenatal care; prospective study; statistical model; Adolescent; Adrenal Cortex Hormones; Adult; Apgar Score; Cohort Studies; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Male; Pregnancy; Prenatal Care; Prospective Studies; Quality of Health Care; Respiratory Therapy